Analisis Laju Erosi dan Tingkat Bahaya Erosi DAS Sekampung Hulu Berbasis GIS (Geographic Information System) - Ridwan, Ridwan; Asmara, Sandi; Satya, Dheo Ihza Amaya (Jurnal Agricultural Biosystem Engineering, 2023)
Soil erosion is a process or event of loss of the upper soil layer, either caused by the movement of water or wind. This erosion process can lead to a deterioration in soil productivity, soil carrying capacity, and environmental quality. The surface of the earth's skin will always experience an erosion process, somewhere there will be erosion while elsewhere there will be hoarding, so the shape will always change all the time. This event occurs naturally and takes place very slowly, so the consequences arise only after decades or even hundreds of years later (Suripin, 2002). This study aims to suspect the erosion rate in the GIS-based Sekampung Hulu watershed, determine the Erosion Hazard Level in the Sekampung Hulu watershed, and describe the distribution of Erosion Rate and Erosion Hazard Level in the Sekampung Hulu watershed. The research was conducted from June to August 2020 at the Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung. The results of the study obtained the results of analysis through GIS application of the highest erosion analysis found in dryland agriculture mixed with shrubs with a very steep slope (>45%) with an area of 1.78 ha. Erosion Hazard Rate in Sekampung Hulu watershed is classified as heavy with a percentage of 33.96% with an area of 14,506.99 ha. Keywords: Erosion, Erosion Hazard Level, Land Use, Slope, Soil, Watershed Area of Sekampung Hulu.